The digital-intercultural-transdisciplinary nexus: Online international exchanges for transdisciplinary education - Tsao, Jack; Alhadad, Sakinah; Heinrichs, Danielle; Abdul Hameed, Suraiya; McLay, Katherine (Australasian Journal of Educational Technology, 2025)
Transdisciplinary problem-solving using digital technologies can further the internationalisation agenda within higher education through an inquiry-based collaborative online international exchange that is transformative and contributes real-world knowledge. Our study focused on a 12-week fully online programme bringing together undergraduates and postgraduates from a Hong Kong university and two Australian universities to research the well-being of university students. Drawing on Pierre Bourdieu’s concepts of field and habitus, we analysed the implementation and effectiveness of digital technologies in influencing the students’ experiences of sharing, learning and collaboration practices. The findings highlight the significance of online learning spaces for intercultural sharing beyond disciplinary spaces and generate tensions and ambiguities that provoke students to critically reflect on comparative cultural and social perspectives. This space for educational exploration and possibilities can move students beyond the taken-for-granted and expose them to diverse viewpoints and ways of thinking conducive to transdisciplinary learning and research. Implications for practice or policy: Higher education institutions and educators can leverage purposefully designed digital technologies and structured online exchange programmes to create equitable international and transdisciplinary collaboration and inquiry spaces. Educators can use multimodal digital technologies, such as collaborative platforms (e.g., Miro, Canva) and creative methods (e.g., digital storytelling, body mapping) for students to engage with ambiguity, negotiate cross-cultural tensions and build critical self-awareness in collaborative settings. Higher education institution policies can support students as co-creators of knowledge.